You look beautiful tonight : a thriller - Jones, Lisa Renee (Thomas & Mercer, 2023)
"Mia Anderson is an invisible woman. An unremarkable thirty-two-year-old Tennessee librarian, she's accustomed to disappearing in a crowd, unseen and unheard. Then she receives an anonymous note: You look beautiful today. It doesn't stop there. The attentive stranger--a secret admirer named Adam--has plans for Mia. With each new text comes a suggestion for her hair, clothes, or attitude, and for the first time in memory, Mia feels noticed. Slowly, she develops a confidence in herself she's never had. But Adam has a surprise coming...and Mia finally sees him for who he is and what he's prepared to do for her. Even kill. Fearing she could be implicated in the murder, Mia's forced to turn to the stranger in the shadows watching her every move. Adam's game of cat and mouse begins with Mia as the prey. In order to survive, she must also become the predator."--Provided by publisher.